Isolation and characterization of the Treponema denticola prtA gene coding for chymotrypsinlike protease activity and detection of a closely linked gene encoding PZ-PLGPA-hydrolyzing activity. - Que, X C (1990)
The chymotrypsinlike protease gene (prtA) from Treponema denticola ATCC 35405 was isolated from a lambda gt11 clone bank as one of several clones expressing protease activity. The DNA from one positive clone capable of hydrolyzing type IV collagen was subcloned into plasmid vector pUC119 for further analysis. Deletion analysis of subclone pXQ27.2 revealed the approximate location of the prtA gene on the DNA insert. DEAE-Sephadex chromatography of crude cell extracts of the subclone revealed two distinct T. denticola enzymes, one hydrolyzing SAAPNA (succinyl-L-alanyl-L-alanyl-L-prolyl-L-phenylalanine-p-nitroanilide [chymotrypsin substrate]) and the other hydrolyzing PZ-PLGPA (phenylazobenzyl-oxycarbonyl-L-leucylglycyl-L-prolyl-D -arginine [collagenase substrate]). Each activity was purified to near homogeneity and exhibited by sodium dodecyl sulfate-polyacrylamide gel electrophoresis estimated molecular sizes of 67 and 36 kDa, respectively. Western blot (immunoblot) analysis demonstrated that only the 67-kDa SAAPNA-hydrolyzing enzyme reacted with antibody against the T. denticola chymotrypsinlike protease. The purified SAAPNA-hydrolyzing enzyme degraded type IV collagen, laminin, and fibronectin, but not type I collagen. These results indicate that the prtA gene coding for the chymotrypsinlike protease from T. denticola has been isolated. Another distinct gene encoding an enzyme hydrolyzing PZ-PLGPA appears to be adjacent to the prtA gene.